Tafsir Al-Qur'an Dalam Perspektif Kaum Feminis (Pemikiran Asma Barlas Dan Kontribusinya Terhadap Perkembangan Hukum Islam) - Abdul Wasik (UNIVERSITAS BONDOWOSO, 2023)
The interpretation of the Qur'an is important in giving meaning to the purpose and purpose of the Qur'an. Because with this interpretation, Muslims can know and even carry out the teachings of Islam as contained in it. On the one hand, admittedly or not, Looking at the mufassir in the classical era, that most of them, or it can be said that all of them are men, so that unconsciously in carrying out their interpretation is always subjective and tends to side with their people (the men) and they do not accommodate the interests of women. Therefore, it is natural that the interpretations produced still reflect patriarchal biases, especially when they are read in the present context. Asma Barlas as one of the female feminist figures appeared to provide solutions, one of which was the need for a re-reading of the texts of the Qur'an whose interpretations were dominated by patriarchal ideology, thus giving rise to the spirit of liberation towards women and upholding the perspective of egalitarianism in the re-reading of verses from the Qur'an. She tried to deconstruct and paradigmatically reconstruct models of interpretation that tend to marginalize the role of women, both in religious, political, and social settings. Asma wants the truth of understanding of how to read religion (the Qur'an) and also wants women to be free from the negative image in Islam as it has been developing. Based on the problems that occurred above, the researcher formulated the following problem: How does the classical era's interpretation of the Qur'an relate to women? And what is the concept of Qur'anic interpretation in Asma Barlas's perspective? Looking at the variables, this study wants to examine the opinions of the mufassir, so this study can be called the character study approach. However, the character study approach is part of qualitative research and the method uses qualitative research as is customary. The study of figures was chosen as an approach, because the researcher wanted to inventory, critically evaluate, and conclude about the thoughts and opinions of the mufassir regarding the concept of Qur'anic interpretation of the Qur'an and Women or gender similarity in the perspketive of the Qur'an.